2023
DOI: 10.1007/s13402-023-00778-w
|View full text |Cite
|
Sign up to set email alerts
|

In-depth quantitative proteomics analysis revealed C1GALT1 depletion in ECC-1 cells mimics an aggressive endometrial cancer phenotype observed in cancer patients with low C1GALT1 expression

Abstract: Background Endometrial cancer (EC) is the most common cancer of the female reproductive organs. Despite the good overall prognosis of most low-grade ECs, FIGO I and FIGO II patients might experience tumor recurrence and worse prognosis. The study of alterations related to EC pathogenesis might help to get insights into underlying mechanisms involved in EC development and progression. Methods Core tumoral samples were used to investigate the role of C1GALT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 84 publications
(108 reference statements)
1
11
0
Order By: Relevance
“…Lin explained that the loss of C1GALT1 inhibited tumor growth in the mouse models of head and neck cancer [ 23 ]. Other studies also demonstrated that C1GALT1 was used to as a biomarker to identify different cancers [ [21] , [24] , [25] ]. C1GALT1 levels were consistent with FGFR3 expression levels, a specific bladder protein, in bladder cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin explained that the loss of C1GALT1 inhibited tumor growth in the mouse models of head and neck cancer [ 23 ]. Other studies also demonstrated that C1GALT1 was used to as a biomarker to identify different cancers [ [21] , [24] , [25] ]. C1GALT1 levels were consistent with FGFR3 expression levels, a specific bladder protein, in bladder cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…C1GALT1 levels were consistent with FGFR3 expression levels, a specific bladder protein, in bladder cancer [ 21 ]. Depletion of C1GALT1 also induced the expression of invasive proteins in endometrial cancer, increasing the invasion ability of cancer cells [ 25 ]. To date, this is the first study to declare the positive regulatory relationship between C1GALT1 and GLUT1.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on endometrial cancer showed that low expression of C1GALT1 induced overexpression of ANXA1 in ECC-1 cells, which were characterized by higher proliferation, invasion, migration, colony formation and angiogenesis ( 79 ). Besides, C1GALT1 is able to modify O-linked glycosylation on integrin α5, thereby modulating activation of the PI3K/AKT pathway in gastric cancer cells ( 80 ). Also in pancreatic cancer, C1GALT1 knockdown significantly inhibited cell adhesion to the extracellular matrix (ECM), which was associated with a decrease in FAK phosphorylation at Y397/Y925 as well as changes in O-glycans on integrins (including β1, αv and α5 subunits) ( 81 ).…”
Section: C1galt1 In Colorectal Cancermentioning
confidence: 99%
“…SPRYD7 and control siRNAs were purchased from Sigma (EHU133421 and SIC001, respectively). For siRNA transfections, 2.5 × 10 5 cells were seeded in culture plates and maintained in DMEM with 10% fetal bovine serum at 37 • C in 5% CO 2 for 24 h, according to established protocols [18,21]. Then, cells were transfected with 22 pmol siRNA using 2 µL JetPrime Transfection reagent in 100 µL of JetPrime buffer.…”
Section: Cloning Sirnas and Transfectionmentioning
confidence: 99%
“…Gain-of-function cell-based assays were performed with CRC cells stably overexpressing SPRYD7, with mock-stably transfected cells as control, as previously described [14,18,21]. Alternatively, loss-of-function cell-based assays were performed 24 h after transient transfection of CRC cells with SPRYD7 or control siRNAs [22].…”
Section: In Vitro Functional Assaysmentioning
confidence: 99%